Identification of receptor-like proteins induced by Sclerotinia sclerotiorum in Brassica napus - Li, Wei; Lu, Junxing; Yang, Chenghuizi; Xia, Shitou (Frontiers in Plant Science, 2022)
Heightening the resistance of plants to microbial infection is a widely concerned issue, especially for economical crops. Receptor-like proteins (RLPs) typically with tandem leucine-rich repeats (LRRs) domain play a crucial role in mediating immune activation, being an indispensable constituent in the first layer of defense. Based on an analysis of orthologs among Brassica rapa, Brassica oleracea, and Brassica napus using Arabidopsis thaliana RLPs as a reference framework, we found that compared to A. thaliana, there were some obvious evolutionary diversities of RLPs among the three Brassicaceae species. BnRLP encoding genes were unevenly distributed on chromosomes, mainly on chrA01, chrA04, chrC03, chrC04 and chrC06. The orthologues of five AtRLPs (AtRLP3, AtRLP10, AtRLP17, AtRLP44, and AtRLP51) were highly conserved, but retrenchment and functional centralization occurred in Brassicaceae RLPs during evolution. The RLP proteins were clustered into thirteen subgroups. Ten BnRLPs presented expression specificity between R and S when elicited by Sclerotinia sclerotiorum, which might be fabulous candidates for Sclerotinia sclerotiorum resistance research.